How to transfer knowledge across the Alps? - Wolfgang Pfefferkorn (Revue de Géographie Alpine)
CIPRA’s Future in the Alps Project aims at showcasing examples of successful implementation and successful projects in the Alps, and making available to others the extensive pool of experience and practical knowledge that lies in these projects. But how to transfer knowledge in an area of some 14 million inhabitants with several linguistic and cultural regions in which thousands of projects are carried out each year, that all kinds of players who work and life in completely different contexts are able to learn and benefit from one another? How do you go about something like that?